Error Analysis in Writing Recount Text by The Eighth Grade Students of SMP Muhammadiyah 4 Surakarta Academic Year of 2015/2016 - Agustina, Tri; , Prof. Dr. Endang Fauziati, M.Hum; , Aryati Prasetyarini, S.Pd, M.Pd (2016)
The study aims to identify the types of morphologicaL,syntactic,discourse error in writing recount text by the eighth grade students of SMP Muhammadiyah 4 Surakarta.In addition, it is to know the frequency of each type of errors, to know the dominant type of error and to know the sources of the errors.The type of research is qualitative research. The method of collecting data is elicitation method, which is divided into four steps: first steps are requesting the learner to make recount text with the theme that has given; second step is reading the recount text made by students;third step is finding and marking error in the recount text; and last step is dividing the error into the types of error based on linguistic category and surface strategy taxonomy.For analyzing the data, the writer takes six steps, namely: identification of errors, classifying into error types, describing the frequency of error, describing the dominant type of error, analysis of the sources of error and describing the purposed remedial teaching. The result of research shows that lexical errors is 22,2% including false friends, wrong spelling and use of Indonesian word. Syntactical error is 64% which include verb (omission of verb,misuses of verb in past tense, addition of to in verb of present tense addition of verb), noun (omission of {-s}plural marker,addition of {-s}), BE (omission of be, misuses of be), phrase (misordering (noun phrase)), article (addition of article), preposition (addition of preposition, omission of preposition), sentence construction (omission of subject, literal translation of Indonesian). Discourse error is 7,7% which include generic structure. The dominant type of error is wrong spelling and misuses of verb in past tense. Key words: error analysis, recount text, surface strategy, linguistic category taxonomy.